Attitude and Orbit Control of a Space Robot at Additional Launching and Approaching a Geostationary Satellite - Somov, Yevgeny; Butyrin, Sergey; Somov, Sergey (Current Chinese Science, 2022)
Background: The problems of putting a space robot into a geostationary orbit using a combined scheme and its approach to a geostationary satellite are considered. The authors’ previous results on this topic are briefly analyzed. Objective: The paper deals with three problems: further development of a rational strategy for the robot’s add-launching on geostationary orbit and its approaching target using a plasma electric propulsion unit only; synthesis of the guidance and control laws; a nonlinear dynamical analysis of the robot’s attitude and orbit control system during these modes. Methods: The developed methods and algorithms are based on the local optimizing the fuel consumption of the plasma electric propulsion unit during each inter-orbital flight of a space robot. Results: Simulation results on the guidance and control algorithms are presented that demonstrate their effectiveness. Conclusion: The breakthroughs are as follows: original strategy of add-launching and forecasting the influence of gravitational disturbances as well as solar pressure forces when synthesizing a robot’s guidance law for its inter-orbital flights.
Keywords: additional launching